2016
DOI: 10.3109/10428194.2016.1166489
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiling identifies mTOR pathway modulation and cytostatic effects of Pim kinase inhibitor, AZD1208, in acute myeloid leukemia

Abstract: Pim kinases phosphorylate and regulate a number of key AML cell survival proteins, and Pim inhibitors have recently entered clinical trial for hematological malignancies. AZD1208 is a small molecule pan-Pim kinase inhibitor and AZD1208 treatment resulted in growth inhibition and cell size reduction in AML cell lines including FLT3-WT (OCI-AML-3, KG-1a, MOLM-16) and FLT3-ITD mutated (MOLM-13, MV-4-11). There was limited apoptosis induction (<10% increase) in the AML cell lines evaluated with up to 3 μM AZD1208 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
4
20
0
Order By: Relevance
“…However, the cooperation between CX-6258 and CX-5461 is consistent with the data of Kirschner and colleagues, showing that PIM kinase inhibition synergizes with agents that induce a p53 response in their mouse model of MYC-driven prostate cancer such as docetaxel and radiation therapy, standard therapies for recurrent prostate cancer (31). In addition, PIM kinase inhibition with CX-6258 led to a decrease in rpS6 phosphorylation, consistent with recent reports that PIM kinases can phosphorylate TSC2, relieving its suppression of MTORC1 activity (36,42). This inhibition of PIM kinase activation of MTORC1 activity may, at least in part, explain the increased potency of CX-6258 in tumor cells with high MTORC1 activity (e.g., PTEN-null cells).…”
Section: Discussionsupporting
confidence: 89%
“…However, the cooperation between CX-6258 and CX-5461 is consistent with the data of Kirschner and colleagues, showing that PIM kinase inhibition synergizes with agents that induce a p53 response in their mouse model of MYC-driven prostate cancer such as docetaxel and radiation therapy, standard therapies for recurrent prostate cancer (31). In addition, PIM kinase inhibition with CX-6258 led to a decrease in rpS6 phosphorylation, consistent with recent reports that PIM kinases can phosphorylate TSC2, relieving its suppression of MTORC1 activity (36,42). This inhibition of PIM kinase activation of MTORC1 activity may, at least in part, explain the increased potency of CX-6258 in tumor cells with high MTORC1 activity (e.g., PTEN-null cells).…”
Section: Discussionsupporting
confidence: 89%
“…Other authors have reported that the effects of AZD1208 on viability and apoptosis vary by cancer type and cell line. In acute myeloid leukemia, AZD1208 induced apoptosis in vitro in some cell lines, but did not induce apoptosis at all in other cell lines [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…PIM kinases expression supports survival of chronic lymphocytic leukemia cells and promotes the CXCR4-mTOR dependent migration [ 44 ]. Similarly, mTOR pathway modulation and AZD1208 cytostatic effects are also identified by protein profiling [ 45 ]. mTOR regulation by PIM kinases and their interrelation in other cancers advocate their magnitude in tumorigenesis.…”
Section: Interrelation Of Pi3k/akt/mtor and Pim Pathways In Other mentioning
confidence: 99%